2011
DOI: 10.1242/jcs.085878
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated missense mutations in bestrophin-1 affect cellular trafficking and anion conductance

Abstract: SummaryBestrophin-1, an integral membrane protein encoded by the BEST1 gene, is localized predominantly to the basolateral membrane of the retinal pigment epithelium. Mutations in the BEST1 gene have been associated with Best vitelliforme macular dystrophy (BMD), a central retinopathy with autosomal dominant inheritance and variable penetrance. Over 120 disease-causing mutations are known, the majority of which result in amino acid substitutions within four mutational hot-spot regions in the highly conserved N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 67 publications
(88 reference statements)
8
62
1
2
Order By: Relevance
“…Upon hypotonic stimulation, the simultaneous activation of the endogenous LRRC8A-mediated VRAC current in HEK293 cells (6, 7) renders it impossible to distinguish endogenous VRACs from heterologously expressed BEST1 currents. To avoid these methodological difficulties, we resorted to Xenopus oocytes, a polarized cell system that provides an important precondition for plasma membrane localization of BEST1 (41). After manual defolliculation and careful monitoring of each single batch for endogenous swellingactivated whole-cell currents, we recorded BEST1-mediated swelling-sensitive currents that were significantly enlarged relative to endogenous I swell .…”
Section: Discussionmentioning
confidence: 99%
“…Upon hypotonic stimulation, the simultaneous activation of the endogenous LRRC8A-mediated VRAC current in HEK293 cells (6, 7) renders it impossible to distinguish endogenous VRACs from heterologously expressed BEST1 currents. To avoid these methodological difficulties, we resorted to Xenopus oocytes, a polarized cell system that provides an important precondition for plasma membrane localization of BEST1 (41). After manual defolliculation and careful monitoring of each single batch for endogenous swellingactivated whole-cell currents, we recorded BEST1-mediated swelling-sensitive currents that were significantly enlarged relative to endogenous I swell .…”
Section: Discussionmentioning
confidence: 99%
“…BEST1, the most studied paralog, was first identified by genetic linkage to a juvenile-onset macular degeneration disease called "Best disease" (6). Nearly 200 mutations in BEST1 have been associated with retinal degenerative disorders, and the vast majority of those that have been characterized cause Cl − channel dysfunction (7)(8)(9)(10)(11). Studies have also indicated that certain bestrophin channels are important for cell volume regulation (12)(13)(14).…”
mentioning
confidence: 99%
“…This coiled-coil domain has been identified as one of the four regions where mutations are associated with disease (42). Some of the mutations in the coiled-coil affect the surface expression of hBest1 in MDCKII cells (47), an expected outcome of disrupted assembly and a clear cause of pathology. However, at least one disease-causing mutation in the coiled coil (R218C) has no effect on the surface expression (47), suggesting that coiled-coil domain has other additional functions in the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the mutations in the coiled-coil affect the surface expression of hBest1 in MDCKII cells (47), an expected outcome of disrupted assembly and a clear cause of pathology. However, at least one disease-causing mutation in the coiled coil (R218C) has no effect on the surface expression (47), suggesting that coiled-coil domain has other additional functions in the channel. We find that transplantation of the coiled-coil domain confers the large current of hBest1 on to hBest3 but only when the coiled coil is accompanied by cotransplantation of Ca 2+ -binding domain of hBest1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation